That's Gotta Hurt : The Injuries That Changed Sports Forever - Geier, Dr. David (Book collections on Project MUSE., 2017)
"The stories of a dozen athletes (including Joan Benoit, Michael Jordan, Brandi Chastain, and Tommy John) whose injuries and recovery advanced the field of sports medicine."--